THE ISSUE OF THE ENFORCEMENT OF JUDICIAL ACTS ISSUED IN RESULT OF JUDICIAL SUPERVISION OVER PRETRIAL PROCEEDINGS - Ghazinyan, Gagik; Danielyan, Ani (State and Law, 2022)
Finality and compulsiveness of judicial acts is a guarantee the legal security of the state, which the RA legislator connects with the legal fact of their entry into legal force. Judicial acts issued in result of judicial supervision over pre-trial proceedings, as judicial acts that do not resolve the case on the merits, enter into force at the moment of their publication, and are binding for execution from the same moment. Judicial acts under consideration at the same time can be revised by appealation and then by cassation.Such regulations are controversial in the context of the principle of legal certainty and the criterion of finality of judicial acts. In addition, in practice, a number of problems arise, both in terms of their implementation after and before exhausting the appeal mechanisms. Moreover, these problems will continue to exist in the conditions of the regulations of the new RA Criminal Procedure Code.Authors have revealed and analyzed a number of issues relating to the topic. As a result of the combined analysis of the essence of legal acts made as a result of judicial supervision over pre-trial proceedings, the principle of legal certainty and the judicial review mechanisms, the authors propose two approaches as a solution of the problem and discuss the possible ways of their implementation in the RA legislation.
Keywords: legal certainty; enforcement of judicial acts; principle of res judicata; pre-trial proceedings; judicial supervision; guarantees of rights; appeal of judicial acts; review of judicial acts; exceptional review